Growth and Selective Etching of Twinned Graphene on Liquid Copper Surface. Issue 40 (13th September 2021) - Liu, Fengning; Dong, Jichen; Kim, Na Yeon; Lee, Zonghoon; Ding, Feng
Abstract: Although grain boundaries (GBs) in two‐dimensional (2D) materials have been extensively observed and characterized, their formation mechanism still remains unexplained. Here a general model has reported to elucidate the mechanism of formation of GBs during 2D materials growth. Based on our model, a general method is put forward to synthesize twinned 2D materials on a liquid substrate. Using graphene growth on liquid Cu surface as an example, the growth of twinned graphene has been demonstrated successfully, in which all the GBs are ultra‐long straight twin boundaries. Furthermore, well‐defined twin boundaries (TBs) are found in graphene that can be selectively etched by hydrogen gas due to the preferential adsorption of hydrogen atoms at high‐energy twins. This study thus reveals the formation mechanism of GBs in 2D materials during growth and paves the way to grow various 2D nanostructures with controlled GBs. Abstract : Growth of ultra‐long straight grain boundaries isotropic liquid surface is ideal for synthesizing 2D materials with ultra‐long straight twin boundaries. The above figure illustrates that when a graphene island grows on a liquid copper surface, ultra‐long straight twin boundaries are formed as expected.